Pembuatan Kompos Daun Dengan Penambahan Stater Inokulum Fungi - Bambang Irawan; Jani Master; Tugiyono; Aspita Laila; Suratman; Salman Farisi (CV. Multi Kreasi Media, 2024)
The Faculty of Mathematics and Natural Sciences (FMIPA) as one of the faculties at the University of Lampung has many trees that produce organic waste in the form of leaf litter every day, and this is very potential to be used as a substrate for compost. Compost is the final substance of a fermentation process of piles of waste/plant litter and sometimes also includes animal carcasses. In the open, compost can occur on its own, through natural processes. However, the process takes a long time while the need for fertile soil is urgent. Therefore, the process needs to be accelerated with the help of microorganisms. This community service activity is a form of application of science and technology by inducing leaf debris as compost material with saprotroph fungi inoculum. Saprotroph fungi isolates are very potential to be developed into composting inoculum in making organic fertilizers. Compost induced with this fungal inoculum is expected to produce organic fertilizer relatively quickly and contain high plant nutrients. The results of the Community Service showed quite good results, namely an increase of about 88.4% from the initial understanding. This is quite interesting because the initial understanding of compost and inoculum was relatively low at 25.04%. After the explanation given by the Community Service team, it was able to be understood by the target audience well so that their understanding increased to 63, 6%.